The Role of Lurah and Mandur as Labor Brokers in the Sugar Plantations of Java (1870–1920) - Ardiansyah (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2026)
The post-1870 expansion of Java's sugar industry required mobilizing seasonal labor at industrial scale from a communal society that knew no land proletariat. This article examines lurah (village heads) and mandur (foremen) as intermediaries who enabled it between 1870 and 1920, asking why the colonial state failed to dismantle a brokerage system it repeatedly acknowledged as exploitative. Building on Eric Wolf's concept of the broker and a historical-institutional approach, it reconstructs the brokerage architecture from three documentary clusters: the Verslag van de Suiker-Enquête Commissie (1921), selected Koloniale Verslagen (1871–1921), and the Mindere Welvaart Onderzoek volumes, read alongside the Kabinetscirculaire of Governor-General Van der Wijck (5 February 1894). The analysis identifies four profit layers of the lurah and three functions of the mandur, and reads state inaction as deliberate prioritization of industrial interests rather than administrative incapacity. Coercion and market mechanisms operated within an institutional architecture framed by colonial policy choices.